Psychological well-being among postgraduate students - Roslan, Samsilah; Ahmad, Nor Aniza; Nabilla, N.; Ghiami, Zeinab (Sciendo, 2017)
This study attempted to determine the level of psychological well-being among postgraduate students. The study also aimed to assess the relationship between psycho-logical well-being and demographic factors, such as age and field of study. Psychological well-being questionnaires were administered to a sample of 192 Master of Education students. The findings demonstrated that Master of Education students possessed a slightly high level of psychological well-being. Differences were found in students’ psychological well-being across age groups, F (4, 167) = 3.178, p = 0.01, and field of study, F (8, 163) = 2.668, p = 0.01, respectively. According to the results, students in the age group of 41 years and above possessed the highest level of psychological well-being (M = 5, SD = 0.71).